2011
DOI: 10.1007/s10526-011-9342-1
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of flonicamide and pymetrozine on five aphid natural enemy species

Abstract: The effects of flonicamide and pymetrozine, on inert and natural substrates, on the rove beetle Aleochara bilineata (Gyll.), the parasitic wasp Aphidius rhopalosiphi (DeStefani-Perez), the ladybird Adalia bipunctata (L.), the carabid beetle Bembidion lampros (Herbst), and the hoverfly Episyrphus balteatus (DeGeer) were assessed in the laboratory. Deltamethrin and pirimicarb were also tested as toxic reference compounds. The results indicated high selectivity of flonicamide and pymetrozine for all the species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 34 publications
3
40
0
1
Order By: Relevance
“…However, Van Driesche et al (2008) and Jansen et al (2011) found direct toxic effects when adults of Aphidius colemani (Viereck) or A. rhopalosiphi, respectively, were exposed to residues on glass plates. Sub-lethal effects in terms of reduced female fertility were reported by Jansen et al (2011), confirming the findings in the present study. Additionally, we observed reduced adult emergence after treatment of M. mediator cocoons.…”
mentioning
confidence: 99%
“…However, Van Driesche et al (2008) and Jansen et al (2011) found direct toxic effects when adults of Aphidius colemani (Viereck) or A. rhopalosiphi, respectively, were exposed to residues on glass plates. Sub-lethal effects in terms of reduced female fertility were reported by Jansen et al (2011), confirming the findings in the present study. Additionally, we observed reduced adult emergence after treatment of M. mediator cocoons.…”
mentioning
confidence: 99%
“…It was reported by [130] that both flonicamid and pymetrozine, did not negatively affect the development time, fertility, and parasitism of a variety of natural enemies including the hoverfly, Episyrphus balteatus; the carabid beetle, Bembidion lampros; the parasitoid, Aphidius rhopalosiphi; the ladybird beetle, Adalia bipunctata; and the rove beetle, Aleochara bilineata under laboratory conditions. In general, pymetrozine exhibited minimal indirect effects on the reproduction of N. californicus under laboratory conditions [121].…”
Section: Selective Feeding Blockersmentioning
confidence: 90%
“…Selective feeding blockers, which include flonicamid and pymetrozine, inhibit the feeding activity of piercing-sucking insects (aphids and whiteflies) after initial insertion of their stylets into plant tissues and interfere with neural regulation of fluid intake through the mouthparts resulting in starvation [125][126][127][128][129][130]. It was reported by [130] that both flonicamid and pymetrozine, did not negatively affect the development time, fertility, and parasitism of a variety of natural enemies including the hoverfly, Episyrphus balteatus; the carabid beetle, Bembidion lampros; the parasitoid, Aphidius rhopalosiphi; the ladybird beetle, Adalia bipunctata; and the rove beetle, Aleochara bilineata under laboratory conditions.…”
Section: Selective Feeding Blockersmentioning
confidence: 99%
“…Also, Jansen et al (2011) reported the side effects of pymetrozine on five natural enemy species of aphids, including coccinellid Adalia bipunctata. These scientists expressed the high selectivity of the insecticide.…”
Section: Lc 50 and Lc 30 Of Insecticidesmentioning
confidence: 99%